Decisions of Women and Society's Elite "Review of Alqur'an Verses (Perspective of Fii Zilalil Qur'an's Interpretation)" - Ihsan, Suryani; Drajat, Amroeni (Academy of Education Journal, 2024)
This study aims to explore and analyze the theme of women's deceit and the elite of society presented in the Qur'an, using an interpretive approach from Tafsir Fii Zhilalil Qur'an by Sayyid Qutb. Through this interpretive study, the researcher seeks to understand how the Qur'an describes the character and strategies used by women and the elite of society in the context of deceit, as well as the moral and social implications contained therein. This study uses a qualitative method with a descriptive-analytical approach to examine relevant verses and interpret their meanings in historical, social, and cultural contexts. The results of the study show that the Qur'an acknowledges the existence of women's deceit as a diverse phenomenon, both carried out by women and the elite of society, and teaches humans to recognize and overcome such deceit through wisdom and strong faith.